After Number 10 - Theakston, K. author. aut Link
VIII, 269 p. 1 illus.
Keywords: Having lost an election, been thrown out by their party, or retired on grounds of ill-health, what do former British prime ministers do? In the first book to look at the lives, political roles and influence of former prime ministers, Theakston analyzes all the former prime ministers from Walpole in the 18th century to Blair today.